A duplex real-time loop-mediated isothermal amplification assay for simultaneous detection of elephant endotheliotropic herpesvirus types 1 and 5 - Xu, Chunzhong; Wang, Ziyan; Zhao, Yongjuan (Frontiers in Veterinary Science, 2025)
Elephant Endotheliotropic Herpesviruses (EEHVs) are the cause of a highly fatal haemorrhagic disease (HD) in elephants primarily affecting young Asian elephants (Elephas maximus) in both captivity and in the wild. Timely and accurate detection of EEHVs is crucial not only for antiviral and supportive treatment, but also for the prevention and control of the EEHV pandemic with proper preventive intervention measures, which requires a simple and rapid assay. EEHVs contain seven genotypes (EEHV1-7), and EEHV1, EEHV4 and EEHV5 are mainly circulating in Asian elephants. Here, we developed a rapid, sensitive and specific duplex real-time LAMP assay for simultaneous detection of EEHV1 and EEHV5. The assay exhibited remarkable specificity with no cross reactions with nine other herpesviruses, and high sensitivity with limit of detection (LOD) of 30 and 189 copies per 25 μL reaction for EEHV1 and EEHV5, respectively. The assay exhibits high reproducibility and can be completed within 30 min, significantly shorter than the qPCR assay. Clinical validation showed that the duplex assay had a 100% concordance with a previously described qPCR assay for 22 samples from Asian and African elephants. Furthermore, no EEHV1 and EEHV5 were detected in elephants at Shanghai Wild Animal Park. The novel duplex LAMP assay represents a particularly valuable POCT tool to facilitate the routine surveillance of EEHV1 and EEHV5 in captive and wild elephants.